Micro Research: Finding sustainable local health solutions in East Africa through small local research studies - MacDonald, Noni E.; Bortolussi, Robert; Kabakyenga, Jerome; Pemba, Senga; Estambale, Benson B.; Kollmann, Martin; Adome, Richard Odoi; Appleton, Mary (Springer International, 2015)
Sub-Saharan African countries are seeking grassroots input to improve health research capacity. A MicroResearch program in East Africa builds local ability to find sustainable solutions for community health problems. The MicroResearch program features three integrated components: (1) 2-week training workshops; (2) development of small proposals with international peer review followed by project funding, implementation, knowledge translation; and (3) coaching from experienced researchers. Evaluation included standardized questions after workshop completion, an online survey of recent workshop participants and discussions at two East Africa MicroResearch Forums in 2013. Between 2008 and 2013, 15 workshops were conducted at five East Africa sites with 391 participants. Of 29 projects funded by MicroResearch, seven are completed; of which six led to changes in local health policy/practice. Program training stimulated 13 other funded research projects including eight external to MicroResearch. The success of MicroResearch sets the stage for potential future growth of such programs.
DOI https://doi.org/10.1007/978-3-319-15750-4_6
Keywords: Knowledge translation; Workshop attendance; Village health team; Volunteer village health; Community health problem